Risk management in POCT blood glucose monitoring: FMEA approach aligned with ISO 15189:2022 - Xiagang Luan; Lingling Ke; Minxuan Feng; Weiqun Peng; Houlong Luo; Hao Xue; Yong Xia (PLoS ONE, 2025)
Objective Point-of-care testing (POCT) blood glucose meters provide rapid and convenient monitoring for clinical care and chronic disease management. However, their accuracy is often compromised by risks associated with personnel, equipment, and procedural inconsistencies. This study systematically assesses these risks using the Failure Mode and Effects Analysis (FMEA) method and proposes control measures aligned with ISO 15189:2022 standards. Methods This study evaluated the risks associated with POCT blood glucose meters in clinical laboratory settings, encompassing the pre-analytical, analytical, and post-analytical phases. A multidisciplinary team employed FMEA to identify potential failure modes and their impacts. A risk matrix classified risks based on probability and severity, with “unacceptable” risks prompting targeted control measures. A follow-up assessment conducted three months later evaluated the effectiveness of these measures through feedback collection and quality control data analysis, ensuring effective risk mitigation in POCT practices. Results The risk assessment identified distinct issues at each hospital: Peking University Shenzhen Hospital faced significant risks related to inadequate performance verification prior to hospital entry, insufficient personnel training, and data management problems, while Wuhan Third Hospital primarily encountered challenges with inadequate training and insufficient calibration and inadequate quality control. Control measures implemented at Peking University Shenzhen Hospital included stringent validation protocols, comprehensive training systems, and automated data management. At Wuhan Third Hospital, the focus was on enhancing training oversight and establishing rigorous quality control measures and calibration Schedule. These interventions effectively reduced unacceptable risks and improved the safety and reliability of the monitoring process. Conclusion Integrating FMEA with ISO 15189:2022 provides a structured approach for identifying and mitigating risks in the use of POCT blood glucose meters. Implementing tailored measures significantly enhances POCT accuracy and reliability, offering clinical institutions effective strategies to improve quality and ensure better patient outcomes.